1997
DOI: 10.1126/science.275.5302.949
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Model Related to Cytochrome c Oxidase and Its Electrocatalytic Four-Electron Reduction of O 2

Abstract: A cytochrome c oxidase model that consists of a cobalt(II) porphyrin with a copper(I) triazacyclononane macrocycle fastened on the distal face and an imidazole covalently attached to the proximal face has been synthesized and characterized. Redox titrations with molecular oxygen (O2) and cobaltocene were carried out, and O2 was found to bind irreversibly in a 1:1 ratio to the model compound. This O2 adduct (a bridged peroxide) can be fully reduced to the deoxygenated form with four equivalents of cobaltocene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
156
1
6

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(165 citation statements)
references
References 16 publications
2
156
1
6
Order By: Relevance
“…In this case, P R and F are also in the same oxidation state, but there is no need for reversible OOO cleavage. Clearly, this model lacks the ferric peroxy form, in contradiction of previous assignments and observations made using synthetic model compounds in which a peroxy species was detected during the the reduction of oxygen to water (41).…”
Section: ϫcontrasting
confidence: 99%
“…In this case, P R and F are also in the same oxidation state, but there is no need for reversible OOO cleavage. Clearly, this model lacks the ferric peroxy form, in contradiction of previous assignments and observations made using synthetic model compounds in which a peroxy species was detected during the the reduction of oxygen to water (41).…”
Section: ϫcontrasting
confidence: 99%
“…In particular, it has been known for five decades that heme/porphyrin-based electrocatalysts (both natural and synthetic) catalyze electrochemical O 2 , H + , and CO 2 reduction (14,(16)(17)(18)(19). Several excellent metalloporphyrin-based O 2 reduction electrocatalysts have been reported, some mimicking natural active sites and some inspired by their design (14,20). Of these catalysts, the Fe-based catalysts generally have provided valuable insights into the O 2 reduction mechanism and a deeper understanding of the structure-function correlations of key enzymes such as CcO, the terminal enzyme in the mitochondrial electron transport chain (1,21).…”
mentioning
confidence: 99%
“…[9] Previously we reported the first functional CcO model that consisted of a Co II ± porphyrin with a Cu I -coordinated distal superstructure and with a covalently attached imidazole group as the axial ligand. [10] We demonstrated that this complex catalyzes the 4 e À reduction of O 2 under physiological conditions without the release of H 2 O 2 . Our electrocatalytic studies also demonstrate that both the copper ion and the axial imidazole ligand are essential to achieve the reduction.…”
mentioning
confidence: 79%